Talent development in adolescent team sports: A review - Burgess, D. J.; Naughton, G. A. (International Journal of Sports Physiology and Performance, 2010)
Traditional talent development pathways for adolescents in team sports follow talent identification procedures based on subjective games ratings and isolated athletic assessment. Most talent development models are exclusive rather than inclusive in nature. Subsequently, talent identification may result in discontentment, premature stratification, or dropout from team sports. Understanding the multidimensional differences among the requirements of adolescent and elite adult athletes could provide more realistic goals for potential talented players. Coach education should include adolescent development, and rewards for team success at the adolescent level should reflect the needs of long-term player development. Effective talent development needs to incorporate physical and psychological maturity, the relative age effect, objective measures of game sense, and athletic prowess. The influences of media and culture on the individual, and the competing time demands between various competitions for player training time should be monitored and mediated where appropriate. Despite the complexity, talent development is a worthy investment in professional team sport.